An affordable and simple method for DNA extraction from agarose suitable for downstream applications - Jesús Enrique Sánchez-Flores; Antonio Sandoval-Cabrera; Patricia Alarcón-Valdés; Jonnathan Guadalupe Santillán-Benítez (Scientific Reports)
Abstract DNA serves as the foundation for molecular biology, leading to the development of numerous molecular techniques. Often, these techniques necessitate the separation and visualization of specific DNA regions. Electrophoresis provides a solution for this requirement. However, the purification of DNA from agarose gels presents a significant challenge, both in terms of complexity and cost. Therefore, here we propose two main protocols that are both cost-effective and efficient based on silica columns or freezing follow by alcohol precipitation. In the case of silica column extraction, the gel was partially or completely dissolved, yielding DNA in most situations. In the case of extraction by freezing and precipitation with ethanol, DNA was obtained in only two out of three treatments. A successful bacterial transformation and PCR were achieved confirmed the suitability of the recovered DNA for further applications.